2022
DOI: 10.1007/s10815-022-02617-7
|View full text |Cite
|
Sign up to set email alerts
|

What to advise to patients with only one good quality blastocyst, PGT-A or not? Outcomes of 2064 cycles

Abstract: Purpose To evaluate whether preimplantation genetic testing for aneuploidy (PGT-A) is beneficial for patients who have only one blastocyst available for biopsy or transfer. Methods This retrospective study was based on 1126 single blastocyst PGT-A and 938 non-PGT-A cycles, a total of 2064 ART cycles which resulted in a single good quality blastocyst in women between 20 and 45 years old. The PGT-A group had 225 single euploid embryo transfer cycles and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The recent article by Kahraman and colleagues [1] reports the results of a study concerning the utility of preimplantation genetic testing for aneuploidy (PGT-A) for couples of poor prognosis who had only 1 blastocyst available. Their study demonstrated that PGT-A had efficacy to distinguish viable and non-viable embryos with various benefits.…”
Section: Sirmentioning
confidence: 99%
“…The recent article by Kahraman and colleagues [1] reports the results of a study concerning the utility of preimplantation genetic testing for aneuploidy (PGT-A) for couples of poor prognosis who had only 1 blastocyst available. Their study demonstrated that PGT-A had efficacy to distinguish viable and non-viable embryos with various benefits.…”
Section: Sirmentioning
confidence: 99%
“…To the Editor, We perceive a need to comment on the study by Kahraman et al, [1] who retrospectively compared the IVF outcomes of patients who had only a single good-quality blastocyst and underwent transfer either with (n = 1126) or without preimplantation genetic testing for aneuploidy (PGT-A) (n = 938). The PGT-A group had 225 and the non-PGT-A group had 938 single euploid embryo transfer cycles.…”
mentioning
confidence: 99%